A Tale of Two Urchins - Implications for In-Situ Breeding of the Endangered Banggai Cardinalfish (Pterapogon kauderni) - Ndobe, Samliok; Jompa, Jamaluddin; Moore, Abigail (Aquacultura Indonesiana, 2018)
The endangered Banggai cardinalfish Pterapogon kauderni, endemic to the Banggai Archipelago in Central Sulawesi, Indonesia, is a national and global priority conservation species. To support stock recovery based on in-situ breeding, using the symbiosis between the Banggai cardinalfish and its microhabitat (especially urchins of Genus Diadema), specific research objectives were: (i) identify the Diadema species associated with Banggai cardinalfish in the wild; (ii) investigate Banggai cardinalfish preference between these Diadema species. Belt transect data (5 sites) found wild Banggai cardinalfish of all size classes associated with Diadema setosum and Diadema savignyi. Preference trials were conducted in a controlled environment (concrete tanks) with three replicates. Nine sub-adult Banggai cardinalfish (35-42 mm SL), 12 D. setosum and 12 D. savignyi were placed in each tank. Banggai cardinalfish association (D. savignyi, D. setosum, none) was recorded hourly (06:00-18:00) for three days and results analysed in RStudio-1.0.143. Banggai cardinalfish did not show significant preference for either D. savignyi or D. setosum. These results indicate that D. savignyi and D. setosum can be used impartially in further research on in-situ breeding to facilitate recovery of Banggai cardinalfish stocks. However stock recovery measures should consider genetic connectivity and the natural balance between the two urchin species.